Model prediction of anterior cruciate ligament force during drop-landings - Pflum, M. A.; Shelburne, K. B.; Torry, M. R.; Decker, M. J.; Pandy, M. G. (Medicine & Science in Sports & Exercise, 2004)
Purpose: The aim of this study was to calculate and explain the pattern of force transmitted to the anterior cruciate ligament during soft-style drop-landings. We hypothesized that peak ACL loading is due to the anterior pull of the quadriceps on the tibia, as these muscles develop large eccentric forces upon impact.